NOVEL MATERIAL: BIOCOMPATIBLE GLUE FOR USE IN BIOLOGY AND MEDICINE—RECOMBINANT MUSSELADHESIVE PROTEINS - Aхambayeva A.S.; Shagyrova , Zh.S.; Nurgozhin , T.S.; Zhienbay , E.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2016)
Mussel adhesive proteins (MFPs) help mussels to attach to various surfaces. Natural MFPs present in the adhesive discs of the byssal threads of the mussels exhibit a number of good adhesiveproperties thatcan be used in medicine, orthodontics, and cell and tissue engineering. MFPs can be used to glue a variety of materials, natural and artificial. For use in medicine, it is important that the MFPs are waterproof adhesives, effectively bonding surfaces submerged in water. Natural MFPs are already being used as adhesives, but their utilization is limited because of high costs. Recombinant MFPs are an attractive alternative because they can be produced in largequantities. For the recombinant MFPs produced by Escherichia coli to possess adhesive properties, post-translational modification of tyrosine residues to 3,4-dihydroxyphenylalanine (DOPA) is required. This paper describes an expression system in which the recombinant adhesive protein Fp-131 is produced, and the newly synthesized polypeptide undergoes modification of the tyrosine residues to DOPA. Hydroxylation of tyrosine occurredin vivo in the bacterial cells because of the activity of tyrosinase, which is coexpressed with Fp-131. Coexpression of Fp-131 and tyrosinase was achieved through the expression of the proteins from two plasmids with different origins of replication and resistance markers. Fp-131 was purified using metal affinity chromatography under denaturing conditions. After dialysis and freeze-drying, a product was obtained with an yield of 25 mg from 1 L of the induced culture. Presence of DOPA was demonstrated in Fp-131 by using a colour reaction with NBT. The adhesion strength of Fp-131 was measured using the lap-shear test. For this test, Fp-131 was used to glue two flat adherends, and a shear load was attached to the glued joint. The adhesive strength was 1.1 MPa, which is comparable to that of natural MFPs.